Does chlorhexidine reduce the incidence of ventilator-associated pneumonia in ICU patients? A systematic review and meta-analysis - Cruz, J. C.; Martins, C. K.; Piassi, J. E.V. [UNESP]; Garcia Júnior, I. R. [UNESP]; Santiago Junior, J. F.; Faverani, L. P. [UNESP] (Elsevier, 2023)
Objective: This study aimed to investigate chlorhexidine's efficacy in preventing ventilator-associated pneumonia (VAP). Design: A systematic review and meta-analysis were conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Settings: The data were obtained from Pubmed, Cochrane Library, and EMBASE. Patients or participants: Only mechanically ventilated patients for at least 48 h were included. Interventions: Randomized clinical trials applying any dosage form of chlorhexidine were eligible. Main variables of interest: The relative risk (RR) of the VAP incidence and all-cause mortality was assessed using the random-effects model. The mean difference in days of mechanical ventilation duration and intensive care unit (ICU) length of stay were also appraised. Results: Ten studies involving 1233 patients were included in the meta-analysis. The oral application of CHX reduced the incidence of VAP (RR, 0.73 [95% CI, 0.55, 0.97]) and did not show an increase in all-cause mortality (RR, 1.13 [95% CI, 0.96, 1.32]). Conclusions: CHX proved effective to prevent VAP. However, a conclusion on mortality rates could not be drawn because the quality of the evidence was very low for this outcome.
¿El cuidado bucal de rutina con clorhexidina reduce la incidencia de neumonía asociada al ventilador en pacientes de la UCI? Una revisión sistemática y metanálisis
Keywords: Antimicrobial agents; Chlorhexidine; Meta-analysis; Ventilator-associated pneumonia